2023
DOI: 10.3390/pharmaceutics15112624
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Changes in Phase II Drug-Metabolizing Enzyme and Drug Transporter Expression during Pregnancy

Christine Gong,
Lynn N. Bertagnolli,
David W. Boulton
et al.

Abstract: The purpose of this literature review is to comprehensively summarize changes in the expression of phase II drug-metabolizing enzymes and drug transporters in both the pregnant woman and the placenta. Using PubMed®, a systematic search was conducted to identify literature relevant to drug metabolism and transport in pregnancy. PubMed was searched with pre-specified terms during the period of 26 May 2023 to 10 July 2023. The final dataset of 142 manuscripts was evaluated for evidence regarding the effect of ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…The impact of physicochemical properties becomes more complex as physiological changes happen during the gestational period [ 108 , 109 ]. Protein binding alterations may be triggered during gestation as far as albumin and alpha1-acid glycoprotein concentrations in both maternal and cord blood are concerned [ 110 , 111 ]. Maternal serum albumin binding appears to decrease, which may lead to an increase in the free proportion of xenobiotics and, thereupon, to elevated placental transfer by passive diffusion [ 110 , 111 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of physicochemical properties becomes more complex as physiological changes happen during the gestational period [ 108 , 109 ]. Protein binding alterations may be triggered during gestation as far as albumin and alpha1-acid glycoprotein concentrations in both maternal and cord blood are concerned [ 110 , 111 ]. Maternal serum albumin binding appears to decrease, which may lead to an increase in the free proportion of xenobiotics and, thereupon, to elevated placental transfer by passive diffusion [ 110 , 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Protein binding alterations may be triggered during gestation as far as albumin and alpha1-acid glycoprotein concentrations in both maternal and cord blood are concerned [ 110 , 111 ]. Maternal serum albumin binding appears to decrease, which may lead to an increase in the free proportion of xenobiotics and, thereupon, to elevated placental transfer by passive diffusion [ 110 , 111 ]. The ratio of albumin concentrations between maternal and fetal serum varies throughout the gestational period, potentially influencing the equilibrium of xenobiotics between these circulations.…”
Section: Resultsmentioning
confidence: 99%
“…The study confirmed that metformin oral clearance was increased in nondiabetic pregnant women with PCOS compared with nonpregnant healthy volunteers or diabetic patients, which resulted in lower plasma metformin concentrations. These results are presumably determined by physiological changes during pregnancy, such as increased renal plasma flow ( 21 ) and possibly enhanced renal expression or function of organic cation transporter 2 ( 22 ), as factors contributing to the increased rate of metformin clearance. As a lower dose is effective for the treatment of prediabetes ( 19 ), the question arises whether it is necessary to adjust the dose in pregnant women with PCOS, bearing in mind that they have a faster elimination of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using buprenorphine and lamotrigine demonstrated that the activities of both phase one and phase two metabolic enzymes are affected by pregnancy, impacting maternal and fetal exposure to these drugs [ 50 , 51 ]. However, the changes in expression levels for phase two enzymes during pregnancy have not been characterized quantitatively yet [ 14 ]. As scientific knowledge evolves, further modeling studies will be performed to evaluate the ability of the pregnancy PBPK model to predict the changes in phase two metabolism in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, Gong et al reviewed the effect of gestational age and hormonal regulation on the expression of phase two enzymes in pregnant woman and the placenta. As part of this review, they identified the current knowledge gaps in phase two enzyme localization, expression, and regulation during pregnancy [ 14 ]. Due to this knowledge gap, predicting the PK in pregnant patients for APIs cleared by phase two metabolic enzymes remains a challenge.…”
Section: Introductionmentioning
confidence: 99%